Wear behavior of TiB2 inoculated 20Cr-3Mo-4C high chromium white cast irons - Yilmaz, Serdar Osman (Springer, 2007)
FeTi, B2O3, Al, and FeW particulates, approximately 40-60 mu m in size, were mixed in stoichiometric ratio and sintered at 1,200 degrees C. The sintered particulates were added as 5 wt% to molten high chromium white cast iron over 50 C-deg above the melting temperature, and stirred at 1,000 rpm. The samples were investigated in three groups: (1) high Cr white cast iron inoculated by the particulates sintered from Al-FeTi-B2O3 particulates; (2) high Cr white cast iron inoculated by the sintered particulates derived from Al-FeTi, B2O3, and FeW particulates; and (3) specimens of the second group that were subsequently homogenized. The microhardness of ceramic particulates was measured as 2,800-3,400 HV10. The effect of sintered particulate volume fraction on the abrasive wear resistance of the high chromium white cast iron was determined. The wear resistance and hardness of the composites improved significantly as a result of particulate inoculation. The application of the homogenization heat treatment to the inoculated samples produced a microstructure having homogeneously distributed particulates.
Keywords: Metal-Matrix Composites; Abrasion Resistance; Alloys; Morphology; Carbides; Fracture